Understanding the Coula edulis, Dacryodes buettneri and Irvingia gabonensis non-timber forest product value chains from Makokou, North-East Gabon from a gender perspective - Yobo, C.M.; Awono, A.; Ingram, V.J. (Commonwealth Forestry Association, 2020)
Trade-in Non-Timber Forest Products (NTFPs) in the Congo Basin is a source of cash income for stakeholders in their value chains, from harvesters to traders. However, gender-disaggregated data on the benefits of such trade in Gabon remains poorly captured and used by policy-makers, despite a decree on women's empowerment enacted by the Republic of Gabon in 2017. This study assesses gender dynamics, reasons for entering the trade, economics, and perceived threats to Coula edulis, Dacryodes buettneri, and Irvingia gabonensis value chains originating in Makokou, Gabon. Data from field observations, key informants, and 79 semi-structured interviews with stakeholders in three markets showed that activities in the value chains of these three NTFPs were highly gender-differentiated. Women dominate in all three chains, particularly in the two lower-value products. This was driven by women's vulnerability and men's preference for higher-value timber and NTFPs. Both men and women enter the trade mostly because they lack other ways to generate income and employment. The men involved in the chains tended to harvest slightly larger volumes and sell at higher prices. The NTFPs and their value chains were all perceived as threatened by climate change, deforestation, and unsustainable forest resources management, with both men and women aware of these threats. The importance of the NTFP trade for women suggested that policies and gender focus interventions, for example on domestication, cultivation, value-adding to improve and sustain their income, could contribute to more sustainable value chains and livelihoods.